Socialization of Innovative Learning Methods to Improve Teacher Competence at Public Elementary School 091488 Bahsampuran, Simalungun Regency - Purnama Sari, Ika; Epi Supriyani Siregar; Anita Purba; Iin Parlina; Rizky Khairunnisa Sormin; Zulia Almaida; Asmarani Nasution (Salus Publica: Journal of Community Service, 2025)
This Community Service Activity aims to improve the Competence of Elementary School Teachers at SD Negeri 091488 in developing innovative learning methods in the classroom. The procedure for the activity carried out by the STIKOM Tunas Bangsa Pematangsiantar Community Service Team is to deliver the material directly and discuss it. The method used in this activity is socialization, which involves conducting various lectures and demonstrations. The data collection technique is in the form of observation to determine whether or not this socialization is necessary. This activity has an outlet so that teachers can design and create innovative learning methods and also know what processes must go through to develop creative learning methods. The participants who took part in this activity were six teachers, one principal, one vice principal, and an administrative staff. These participants are teachers from SD 091488 Bahsampuran, Simalungun. The results obtained from this Community Service activity showed active participation, where teachers seemed very enthusiastic about the material presented by the resource person. his Community Service Activity aims to improve the Competence of Elementary School Teachers at SD Negeri 091488 in developing innovative learning methods in the classroom. The procedure for the activity carried out by the STIKOM Tunas Bangsa Pematangsiantar Community Service Team is to deliver the material directly and discuss it. The method used in this activity is socialization, which involves conducting various lectures and demonstrations. The data collection technique is in the form of observation to determine whether or not this socialization is necessary. This activity has an outlet so that teachers can design and create innovative learning methods and also know what processes must go through to develop creative learning methods. The participants who took part in this activity were six teachers, one principal, one vice principal, and an administrative staff. These participants are teachers from SD 091488 Bahsampuran, Simalungun. The results obtained from this Community Service activity showed active participation, where teachers seemed very enthusiastic about the material presented by the resource person.